Minimum pilot power for service coverage in WCDMA networks - Siomina, Iana; Yuan, Di (Wireless networks, 2008)
Pilot power management is an important issue for efficient resource utilization in WCDMA networks. In this paper, we consider the problem of minimizing pilot power subject to a coverage constraint. The constraint can be used to model various levels of coverage requirement, among which full coverage is a special case. The pilot power minimization problem is -hard, as it generalizes the set covering problem. Our solution approach for this problem consists of mathematical programming models and methods. We present a linear-integer mathematical formulation for the problem. To solve the problem for large-scale networks, we propose a column generation method embedded into an iterative rounding procedure. We apply the proposed method to a range of test networks originated from realistic network planning scenarios, and compare the results to those obtained by two ad hoc approaches. The numerical experiments show that our algorithm is able to find near-optimal solutions with a reasonable amount of computing effort for large networks. Moreover, optimized pilot power considerably outperforms the ad hoc approaches, demonstrating that efficient pilot power management is an important component of radio resource optimization. As another part of our numerical study, we examine the trade-off between service coverage and pilot power consumption.